Use of Technological Aids in the Resection of a Rare Maxillofacial Tumor of Infancy. (October 2018) - Gillenwater, Justin; Harshbarger, Raymond
Melanotic neuroectodermal tumor of infancy is a rare maxillofacial tumor, usually presenting within the first year of life, often a benign locally aggressive lesion, with wide local excision providing the best opportunity of cure. In past reports, direct tissue visualization guided resection, with occasional need for reoperation to clear margins. In this case report, a method is presented to achieve clear margins in surgery using virtual surgical planning and surgical stealth navigation.